“Ubi proceditur ex praesumptionibus minuitur poena”. Quality of the evidence and quantity of the penalty according to the Doctrina Innocentii: Peer-reviewed article (Italian Review of Legal History, 2021)
In Roman-Canonical inquisitorial process, a strict application of the law of proof would have made it impossible to convict a defendant on the basis of circumstantial evidence. This posed many obstacles to the administration of a criminal justice system oriented to the principle of public interest in the prosecution of crimes. A statement of Innocent IV found in the commentary to c. Quia verisimile (X 2.23.10) opened the way to presumptive conviction: the judge could condemn the defendant in the absence of full evidence, as long as he reduced the sentence. In its original formulation, Innocent’s sentence represented no more than a cautionary recommendation. It was the doctrinal elaboration that transformed it, beyond the intentions of its author, into an instrument capable of affecting the theoretical rigidity of the system, admitting discretion in modulating the penalty and applying a punishment even in situations of lack of evidence. In this debate, which the present study intends to analyze in its fundamental stages, the contribution of the decretalists has had a leading weight: this way, too, the central role assumed by canonical teaching in the doctrinal reflection on the theory of the law of proof is revealed.
Keywords: Romano-canonical procedure; criminal justice; presumptions; lack of evidence; probatio presuntiva; extraordinary punishment; Innocent IV